1st International Fuel Cell Science, Engineering and Technology Conference 2003
DOI: 10.1115/fuelcell2003-1729
|View full text |Cite
|
Sign up to set email alerts
|

A Silicon Microfabricated Direct Formic Acid Fuel Cell

Abstract: A silicon-based microfabricated fuel cell running on formic acid has been developed to provide a high energy and power density power source on the millimeter size scale. A polymer electrolyte membrane fuel cell was fabricated utilizing the Nafion™112 membrane bonded between electrodes on silicon substrates. The cell was fueled by a concentrated formic acid-water solution and the catalyst used was Pt. The preliminary result shows that the microfabricated formic acid fuel cell may be a promising alternative for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Our results should be analysed and compared to each other and to those obtained using silicon-based microtechnology in the literature [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. To do this, we calculate a figure of merit termed the fuel use efficiency [40] from the current density (mW cm −2 ) at maximum power density, the active cell surface (cm 2 ) and the fuel flow rate (mol s −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results should be analysed and compared to each other and to those obtained using silicon-based microtechnology in the literature [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. To do this, we calculate a figure of merit termed the fuel use efficiency [40] from the current density (mW cm −2 ) at maximum power density, the active cell surface (cm 2 ) and the fuel flow rate (mol s −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the former we have Kelley et al [17] who achieved a power density of 12 mW cm −2 at a rather large fuel flow rate of 2000 μL min −1 . Yeom et al [23] achieved 0.38 mW cm −2 at a fuel flow rate of 1000 μL min −1 and Yen et al [18] achieved 47.2 mW cm −2 for dry-etched silicon microchannels (750 μm width by 400 μm depth) operating at 60 • C, but this fell to 12 mW cm −2 at room temperature for a fuel flow rate of 283 μL min −1 corresponding to a fuel use efficiency of 4.7%. However, a notable recent result is Wong et al [26] who demonstrated a power output of 34 mW cm −2 for a 1 cm 2 serpentine silicon-microchannel-based system at a fuel flow rate of 800 μL min −1 (fuel use efficiency = 1.9%); this group also showed that a smaller microchannel height coupled with a serpentine microchannel rather than parallel channels improves cell performances, but the results were again generated at a relatively high fuel flow rate of 800 μL min −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the cost for the materials is low and the structure of the cell is simple. Since formic acid fuel cells are capable of delivering higher energy densities than the most competitive rechargeable batteries [15] and can easily be obtained from fossil fuels, such as natural gas or coal, as well as from existence sources through fermentation of agricultural products and from biomasses, we use formic acid as a fuel to study the performance of MLSPBFC in this work. This is an important metric in the development of converged electronic devices as the operating time is becoming limited by conventional battery technology.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent papers [1][2][3][4][5] have shown the growing interest in the development of MEMS and CMOS compatible processes for the fabrication of small fuel cells for the range of energies required (1-10 W) and below. These fuel cells mostly used Nafion ® or an equivalent ionomer as the proton exchange membrane.…”
Section: Introductionmentioning
confidence: 99%